Modification of the Expression of the Aquaporin ZmPIP2;5 Affects Water Relations and Plant Growth . Issue 4 (24th January 2020) - Ding, Lei; Milhiet, Thomas; Couvreur, Valentin; Nelissen, Hilde; Meziane, Adel; Parent, Boris; Aesaert, Stijn; Van Lijsebettens, Mieke; Inzé, Dirk; Tardieu, François; Draye, Xavier; Chaumont, François
Abstract : The maize plasma membrane PIP2;5 aquaporin plays a role in controlling root radial water movement, leaf hydraulic conductivity, and plant growth. Abstract: The plasma membrane intrinsic protein PIP2;5 is the most highly expressed aquaporin in maize ( Zea mays ) roots. Here, we investigated how deregulation of PIP2;5 expression affects water relations and growth using maize overexpression (OE; B104 inbred) or knockout (KO; W22 inbred) lines. The hydraulic conductivity of the cortex cells of roots grown hydroponically was higher in PIP2;5 OE and lower in pip2;5 KO lines compared with the corresponding wild-type plants. While whole-root conductivity decreased in the KO lines compared to the wild type, no difference was observed in OE plants. This paradox was interpreted using the MECHA hydraulic model, which computes the radial flow of water within root sections. The model hints that the plasma membrane permeability of the cells is not radially uniform but that PIP2;5 may be saturated in cell layers with apoplastic barriers, i.e. the endodermis and exodermis, suggesting the presence of posttranslational mechanisms controlling the abundance of PIP in the plasma membrane in these cells. At the leaf level, where the PIP2;5 gene is weakly expressed in wild-type plants, the hydraulic conductance was higher in the PIP2;5 OE lines compared with the wild-type plants, whereas no difference was observed in the pip2;5 KO lines. The temporal trend of leaf elongation rate, used as a proxy for that of xylem water potential, was faster in PIP2;5 OE plants upon mild stress, but not in well-watered conditions, demonstrating that PIP2;5 may play a beneficial role in plant growth under specific conditions.